Institutional Ownership and Intellectual Capital Determining Factors in the Value of Textile and Garment Companies - Putri, Aurrel Azalea Cesarena; Hendaris, Raden Budi (Universitas Kristen Maranatha, 2024)
Purpose – This study investigates the influence of institutional ownership and intellectual capital on the valuation of textile and garment manufacturing firms listed on the Indonesia Stock Exchange (BEI) between 2018 and 2022. Design/Methodology/Approach - This research is a quantitative study that employs secondary data obtained from literature and documentation investigations. The data for this research was acquired from the IDX website and the official websites of each firm listed on the Indonesia Stock Exchange between 2018 and 2022. The research sample comprised 14 companies, from which a total of 70 data points were collected using purposive sampling. Data analysis encompasses several statistical techniques such as classical assumption testing, multiple linear regression, correlation, determination, partial tests, and simultaneous tests. These techniques are performed using IBM SPSS version 26 software. Findings - The research findings indicate the presence of institutional ownership exerts a detrimental influence on the overall value of a company. Conversely, intellectual capital has a beneficial influence on the value of a corporation. Research Limitations/Implications - The impact of the following research is that it can become a basis for developing knowledge about company value as additional information and consideration in an investment. However, the limited availability of data, particularly when organizations do not supply comprehensive and reliable information, diminishes the statistical power of research. This, in turn, decreases the likelihood of discovering a genuine association, making it difficult to make generalizable conclusions. Keywords: Institutional Ownership, Intellectual Capital, Company Value